Effects of Smoking and HLA-B51 on Clinical Manifestations in Behçet’s Disease: Retrospective Analysis of 209 Patients in a Turkish Population - Serpil TUNA,; Sevil ALAN,; Elif Betül TÜRKOĞLU, (Archives of Rheumatology, 2015)
Objectives: This study aims to investigate the separate and cumulative effects of smoking and human leukocyte antigen (HLA)-B51 on the severity and clinical manifestations of Behçet’s disease (BD). Patients and methods: A total of 209 patients (119 males, 90 females; mean age 42.97±10.44 years; range 23 to 75 years) with BD were included in this retrospective study. The severity and clinical manifestations of BD, smoking habits, and presence of HLA-B51 of patients were obtained from medical records. The severity of BD was evaluated with Behçet’s Syndrome Activity Scale (BSAS). Relationship between smoking habits and presence of HLA-B51 with disease severity and clinical manifestations was investigated. Results: Presence of HLA-B51 was effective on BSAS, erythema nodosum (EN), articular, ocular and neurological involvements (p=0.001, p=0.011, p=0.013, p=0.001, p=0.038, respectively). Smoking was also effective on BSAS, EN, articular, ocular and neurological involvements (p=0.001, p=0.001, p=0.013, p=0.042, p=0.027, respectively). There was a strong association between positive HLA-B51 with smoking (p=0.004). Smoking and HLA- B51 were effective on articular involvement, smoking was effective on EN, and HLA-B51 and smoking were effective on ocular and neurological involvements (p=0.039, p=0.040, p=0.001, p=0.028, p=0.037, respectively). Conclusion: Our findings indicate that smoking and HLA-B51 influence severity and systemic involvements of BD with a positive relationship in between. We recommend that smoking and HLA-B51 should be considered simultaneously in BD since this relationship may lead to incorrect inferences.